Plasmodium knowlesi malaria an emerging public health problem in Hulu Selangor, Selangor, Malaysia (2009-2013): epidemiologic and entomologic analysis - Vythilingam, Indra; Lim, Yvonne Ai Lian; Venugopalan, Balan; Ngui, Romano; Leong, Cherng Shii; Wong, Meng Li; Loke, Tim Khaw; Goh, Xiang Ting; Yap, Nan Jiun; Wan Sulaiman, Wan Yusoff; Jeffery, John; Ab Ghani, CT Zawiah; et al. (BioMed Central, 2014)
BACKGROUND: While transmission of the human Plasmodium species has declined, a significant increase in Plasmodium knowlesi/Plasmodium malariae cases was reported in Hulu Selangor, Selangor, Malaysia. Thus, a study was undertaken to determine the epidemiology and the vectors involved in the transmission of knowlesi malaria. METHODS: Cases of knowlesi/malariae malaria in the Hulu Selangor district were retrospectively reviewed and analyzed from 2009 to 2013. Mosquitoes were collected from areas where cases occurred in order to determine the vectors. Leucosphyrus group of mosquitoes were genetically characterized targeting the nuclear internal transcribed spacer 2 (ITS2) and mitochondrial cytochrome c oxidase subunit I (CO1). In addition, temporal and spatial analyses were carried out for human cases and vectors. RESULTS: Of the 100 microscopy diagnosed P. knowlesi/P. malariae cases over the 5 year period in the Hulu Selangor district, there was predominance of P. knowlesi/P. malariae cases among the young adults (ages 20-39 years; 67 cases; 67%). The majority of the infected people were involved in occupations related to agriculture and forestry (51; 51%). No death was recorded in all these cases.Five hundred and thirty five mosquitoes belonging to 14 species were obtained during the study. Anopheles maculatus was the predominant species (49.5%) followed by Anopheles letifer (13.1%) and Anopheles introlatus (11.6%). Molecular and phylogenetic analysis confirmed the species of the Leucosphyrus group to be An. introlatus. In the present study, only An. introlatus was positive for oocysts. Kernel Density analysis showed that P. knowlesi hotspot areas overlapped with areas where the infected An. introlatus was discovered. This further strengthens the hypothesis that An. introlatusis is the vector for P. knowlesi in the Hulu Selangor district.Unless more information is obtained on the vectors as well as macaque involved in the transmission, it will be difficult to plan effective control strategies. The utilization of modern analytical tools such as GIS (Geographic Information System) is crucial in estimating hotspot areas for targeted control strategies. CONCLUSIONS: Anopheles introlatus has been incriminated as vector of P. knowlesi in Hulu Selangor. The cases of P. knowlesi are on the increase and further research using molecular techniques is needed.